2017
DOI: 10.1107/s1600577517001540
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic design and modelling of a 14 mm-period prototype superconducting undulator

Abstract: The magnetic design of a ten-period (each period 14 mm) prototype superconducting undulator is reported using RADIA. The results of modelling the magnetic flux density are presented in an analytical formula. The dependence of the field integrals and phase error on the current density and undulator gap has been calculated, and temperature curves are determined for the models and are compared with earlier reported Moser-Rossmanith fits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This technology is by now mature enough to be applied in a UC-XFEL. Other standard approaches to undulator development may include superconducting undulators, where designs with periods nearing those needed have been studied [152]. At few-mm period length, development work on novel variations on short period Halbach arrays is being pursued [59].…”
Section: Discussionmentioning
confidence: 99%
“…This technology is by now mature enough to be applied in a UC-XFEL. Other standard approaches to undulator development may include superconducting undulators, where designs with periods nearing those needed have been studied [152]. At few-mm period length, development work on novel variations on short period Halbach arrays is being pursued [59].…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Rossmanith et al first adopted the boundary integral method-based RADIA code (implemented in Mathematica) for the magnetic field calculation of an in-vacuum planar SCU [141]. Further studies based on RADIA code were reported for the magnetic design or field optimization of planar SCU [59,[142][143][144], hybrid planar-tilted SCU [117,120], staggered-array BHTSU [108], Delta-like SCAPE undulator [125] and NbTi helical SCU [13]. In 2002, Caspi et al first adopted the finite element method (FEM) software TOSCA/OPERA 2D for the magnetic design of helical windings based planar SCU [145].…”
Section: Modelling Toolsmentioning
confidence: 99%
“…Other scaling laws were later proposed by Kim for a planar SCU with fixed Jλ [157] and by Mishra for a 14 mm period planar SCU based on the formula for a hybrid PM undulator [144]. In 2014, Kinjo et al presented an analytical formula equation ( 6) for calculating the on-axis field B 0 in a staggeredarray bulk HTSU and validated it through experiments…”
Section: Scaling Lawsmentioning
confidence: 99%
“…In recent years, most SCU research has focused on lowtemperature superconductors (LTS) such as Nb 3 Sn [2][3][4][5][6][7] and NbTi [8][9][10] SCUs. These conductors have good performance in the field, but unfortunately, they need to be operated at low temperatures; they have very little temperature margin, which makes cryocooled operation difficult [4,7,11].…”
Section: Introductionmentioning
confidence: 99%